Monitoring Corruption Trials: The Joint Efforts of Higher Education Institutions and Courts in Indonesia - Adi Tirto Koesoemo; Vicky Fransiskus Taroreh; Selviani Sambali (Borong Newinera Publisher, 2023)
In order to create a clean and transparent judiciary as a form of achieving legal objectives (certainty, usefulness and justice), the Indonesian Corruption Eradication Commission collaborates with several universities throughout Indonesia to carry out audio and visual recording of Corruption Crime trials. The aim of this activity, apart from being a form of monitoring from the judicial side, is also to be used as study material for students involved in this recording activity to deepen their study of criminal procedural law. This research produces a study in the form of empirical data on the benefits of recording corruption trials. In the research, it was stated that this trial monitoring activity was systematically carried out because in legal substance it had received legal recognition. The results of the study found that the implementation of KPK supervision in handling corruption cases in the regions was able to be realized well.